Influence of pre-harvest fruit bagging on Golden Delicious apple (Malus × domestica) - SHARMA, R R; ASREY, RAM; SAGAR, V R; SETHI, SHRUTI (The Indian Journal of Agricultural Sciences, 2017)
Studies were conducted to observe the effect of pre-harvest fruit bagging on Golden Delicious apples. For this, Golden Delicious apples were bagged on 60, 75 and 90 days after full bloom (DAFB), and bags were removed five days before harvesting. Our results revealed that apples bagged on 60, 75 and 90 DAFB matured 15, 10 and 3 days earlier than non-bagged apples. The incidence of Sanjose scale (2.6 ± 0.2 %), scab (6.3 ± 0.4 %), sooty mold (0 ± 0 %) and fly speck (2.8 ± 0.2 %) was the least in apples bagged on 60 DAFB than non-bagged apples. Apples bagged on 60 DAFB, developed appealing golden colour (Hunter ‘b’ value = 58 ± 2.2) than those bagged on later dates or non-bagged ones (Hunter ‘b’ value = 28 ± 1.5). Similarly, apples bagged on 60 DAFB were less firm (32.4 ± 1.6 N) but had higher levels of anthocyanins and exhibited high antioxidant activity (14.6 ± 0.4 μmol Trolox/g FW) than apples bagged on later dates or non-bagged apples with slight improvement in quality attributes. Thus, it can be concluded that pre-harvest fruit bagging in Golden Delicious apple on 60 days after full bloom is the best practice to get attractive golden coloured fruits with least incidence of insects and diseases and improved fruit quality.